The Analysis of Nutmeg Mace Essential Oil Compound Using GC-MS and Antibacterial Activity Test Toward Ecschericia coli and Staphylococcus aureus - Nur ‘Aini Hidayah; Hery Muhamad Ansory; Prietta Khania Kusuma Putri; Anita Nilawati (Majalah Farmaseutik, 2017)
Isolation of essential oil from nutmeg mace by using water distillation method had been done. The content analysis of the nutmeg mace essential oil compound was done by using GC-MS. The analysis result shows that there are 4 dominant compounds they are α-pinene, sabinene, 2-β-pinen, and myristicin. The quality of nutmeg mace essential oil is seen from the ratio of oil resulted from isolation with the SNI standard. Nutmeg mace essential oil does not fulfill the SNI standard in term of specific weight. However, it contains a relatively high among of myristicin which is 30.82%. According to Agusta (2000), essential oil is a good antibacterial. The antibacterial activity test was done by using the dilution and diffusion method. The result of the dilution test could not conclude the value of KHM and KBM. The diffusion test result shows that nutmeg mace essential oil with 7.5% concentration is able to inhibit the growth of Stapylococus aureus with the average inhibition zone diameter of 9.25 mm. While on the Ecschericia coli bacteria, it has the average inhibition zone diameter of 7.375 mm.